Takhrij and Syarah Hadith Agrotechnology: Irrigation on Agriculture - Tridesi Rhamdani Sumantri; Wahyudin Darmalaksana; Mi'raj Fuadi (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a type of qualitative through library and field studyapproach. Takhrij and commentary tradition The results and discussion of this research is important agricultural irrigation for farmers. The conclusion of this research is that the takhrij and syarah hadith emphasize agriculture by utilizing natural resources, namely water to increase production by using the irrigation system method.